Uslub Iltifât dalam Alquran - Zaenuddin, Mamat (TAJDID, 2018)
The research is aimed at the discovery of the development in the field of uslubiltifat in Alquran, characteristics of uslubiltifat in Alquran, the beauty of uslubiltifat in Alquran, the new concept about uslubiltifat. Through quantitative analysis, this research suggests that uslub iltifat in Alquran develops in the field of already existing uslubiltifat by making iltifat 'adaddhamir(change in the pronominal numerals) and iltifat anwa al-jumlah (the change in a variety of sentences) as a part of it. Characteristics of uslub iltifat in Alquran is a miracle of Alquran, because Alquran is not a magic, but it has characteristics of magic; a strength of feeling or emotion and affection. The beauty of uslubiltifat in Alquran has reached such the top level that the language of human can not afford to compete with it. As a result of this research, the new concept of iltifat says: Gaya bahasa (figure of speech) with a use of a change from thefirst sentence to the following sentence with the point being related to the first sentence with the aim of putting great emphasis on the beauty of Balaghah.